Conservation Agriculture Affects Grain and Nutrient Yields of Maize (Zea Mays L.) and Can Impact Food and Nutrition Security in Sub-Saharan Africa - Galani, Yamdeu Joseph Hubert; Ligowe, Ivy S.; Kieffer, Martin; Kamalongo, Donwell; Kambwiri, Alfred Mexon; Kuwali, Pamela; Thierfelder, Christian; Dougill, Andrew J.; Gong, Yun Yun; Orfila, Caroline (Frontiers in Nutrition, 2022)
Maize is a major staple and plays an essential role in food and nutrition security in sub-Saharan Africa. Conservation agriculture (CA), a climate-smart agriculture practice based on minimum soil disturbance, crop residue retention, and crop diversification, has been widely advocated but without extensive research on the impact it may have on maize nutrient composition, food and nutrition security. This study assessed the grain yield, macro and micronutrient mineral content and nutrient yield of 8 maize varieties grown in Malawi, and how these are affected by CA practices over two seasons. The minerals were analysed using inductively coupled plasma (ICP) coupled to optical emission spectroscopy (OES) and to mass spectroscopy (MS). Grain yield and Se content differed among the varieties, while C, N, Fe, K, Mg, Mn, P and Zn were similar. The local variety Kanjerenjere showed the lowest grain and nutrient yields. The open-pollinated varieties concentrated more minerals than the F1 hybrids, but the latter showed higher yields for both grain and nutrients. Typical consumption of the 8 maize varieties could fully meet the protein and Mg dietary reference intake of Malawian children (1-3 years), as well as Mg and Mn needs of adult women (19-50 years), but their contribution to the dietary requirements was low for Fe (39-41%) and K (13-21%). The trials showed that CA increased grain yield (1.2 to 1.8-fold) and Se content (1.1 to 1.7-fold), but had no effect on C, K, Mg, P and Zn, and reduced N (1.1 to 1.2-fold), Mn (1.1 to 1.8-fold), and Fe (1.3 to 3.4-fold). The high increase of grain yield under CA treatments resulted in increased yields of protein and Se, no effect on the yields of K, Mg, Mn, P and Zn, and reduced Fe yield. CA could contribute in reducing the risk of Se deficiency in Malawian women and children, but exacerbate the risk of Fe deficiency. A combination of strategies will be needed to mitigate some of the foreseen effects of climate change on agriculture, food and nutrition security, and to improve nutrient intake.